UAE English Skills: A Textbook Evaluation - Al Falasi, Hessa Ghanem (2008)
A Master of Arts Thesis in Teaching English to Speakers of Other Languages (TESOL) by Hessa Ghanem Al Falasi Entitled, "UAE English Skills: A Textbook Evaluation," January 2008. Available are both Hard and Soft Copies of the Thesis.